Joint statement for assessing and managing high blood pressure in children and adolescents: Chapter 1. How to correctly measure blood pressure in children and adolescents - Lurbe, Empar; Mancia, Giuseppe; Calpe, Javier; Drożdż, Dorota; Erdine, Serap; Fernandez-Aranda, Fernando; Hadjipanayis, Adamos; Hoyer, Peter F.; Jankauskiene, Augustina; Jiménez-Murcia, Susana; Litwin, Mieczysław; Mazur, Artur; et al. (Frontiers in Pediatrics, 2023)
The joint statement is a synergistic action between HyperChildNET and the European Academy of Pediatrics about the diagnosis and management of hypertension in youth, based on the European Society of Hypertension Guidelines published in 2016 with the aim to improve its implementation. The first and most important requirement for the diagnosis and management of hypertension is an accurate measurement of office blood pressure that is currently recommended for screening, diagnosis, and management of high blood pressure in children and adolescents. Blood pressure levels should be screened in all children starting from the age of three years. In those children with risk factors for high blood pressure, it should be measured at each medical visit and may start before the age of three years. Twenty-four-hour ambulatory blood pressure monitoring is increasingly recognized as an important source of information as it can detect alterations in circadian and short-term blood pressure variations and identify specific phenotypes such as nocturnal hypertension or non-dipping pattern, morning blood pressure surge, white coat and masked hypertension with prognostic significance. At present, home BP measurements are generally regarded as useful and complementary to office and 24-hour ambulatory blood pressure for the evaluation of the effectiveness and safety of antihypertensive treatment and furthermore remains more accessible in primary care than 24-hour ambulatory blood pressure. A grading system of the clinical evidence is included.